Mouthguard-effect of high-intensity weight training on masticatory muscle tone and stiffness in taekwondo athletes - Wang, J.-S.; Seo, D.-W.; Cha, J.-Y. (Journal of Exercise Rehabilitation, 2020)
This study aimed to analyze the effect of wearing a mouthguard or not on masticatory muscle tone and stiffness of male taekwondo athletes during high-intensity weight training. The participants were male taekwondo athletes and aged 18 to 22 years. We randomly divided 24 men into the control group (CON; without a mouthguard; n=12) and the experimental group (MOG; with a mouthguard; n=12). Masticatory muscle tone and stiffness were measured after weight training at a level of 70% of one-repetition maximum. As a result of this study, masticatory muscle tone was no different in intragroup and intergroup after experiment. In addition, although the masticatory muscle stiffness was significantly higher in the dominant side of the MOG, there was no difference in intergroup, intragroup, and interaction. Through this study, it is necessary to consider the selective wearing of a mouthguard according to the training methods when partially analyzed from the physiological point of view of the masticatory muscle of taekwondo athletes.